Change Management for Enhancing the Quality of Educational Administrative Services in Islamic Secondary Schools - lindiana; Abdul Hamid; Arifia Retna Yunita (Al-Qalam Institue, 2026)
This research is motivated by the importance of improving the quality of educational administration services in Madrasas in response to the demands of technological advances and public expectations for fast, accurate, and transparent services. Private aliyah madrasas strive to implement change management to improve the quality of administrative services, but face various obstacles such as limited infrastructure, digital competency gaps, and resistance to change. This study aims to analyze the application of change management through the functions of planning, organizing, implementing, and supervising in improving the quality of education administration services, as well as identifying supporting and inhibiting factors. The research uses a descriptive qualitative approach with observation, interview, and documentation data collection techniques. The results of the study show that change planning is carried out systematically and participaly, the implementation of change through the regulation of human resources and information technology has a positive impact on service efficiency, but multidimensional obstacles are still found. In conclusion, planned and participatory change management has been proven to be effective in improving the quality of administrative services. This research contribution enriches change management theory by integrating the functions of POAC and Islamic values, as well as providing a practical model for madrasas in the administrative transformation of education administration.